Pengaruh Lingkungan Kerja, Kompensasi dan Kepuasan Kerja Terhadap Kinerja Karyawan Perawat RSUD - Nanda Meisya; Edy Purwo Saputro (Journal of Trends Economics and Accounting Research, 2023)
This research aims to determine: (1) the influence of the work environment on the performance of nurses at RSUD Dr. SOEDONO Madiun, (2) the influence of compensation on the performance of nurses at RSUD Dr. SOEDONO Madiun and (3) the influence of Job Satisfaction on the Performance of Nurses at RSUD Dr. SOEDONO Madiun. This research was conducted using quantitative methods with data collection techniques using questionnaires. The sampling technique uses purposive sampling technique. Test validity and reliability using smart PLS analysis on the outer model. Hypothesis testing uses the smartPLS inner model. The research results show that the variable X1 Environment has a positive relationship with the dependent variable Performance (Y), X2 Compensation has an insignificant positive effect on the Performance variable (Y). This research only tests several independent variables, namely Work Environment, Compensation and Job Satisfaction. This research is specifically aimed at employees, especially nurses at RSUD dr. Soedono Madiun only so it cannot be addressed to the public.